A plasticity theory and finite element implementation of friction model - Ahmad Kamal Ariffin Mohd Ihsan, (1998)
A friction model based on plasticity theory is presented. An interface element was used in the finite element implementation. An incremental-iterative solution strategy was suggested to simulate the non-linear problem in friction. The model was tested to simulate the friction force of the ejection of a powder compact component from a die. The numerical simaulation results were validated and shows good agreement